Sr4N[CN2][C2N]: The First Carbodiimide Acetonitriletriide - Jach, Franziska; Hoehn, Peter; Prots, Yurii; Ruck, Michael (European Journal of Inorganic Chemistry, 2019)
The acetonitriletriide anion C 2 N 3– , the fully deprotonated form of acetonitrile, is stabilized in a pure alkaline earth metal environment in Sr 4 N[CN 2 ][C 2 N]. The heterogeneous reaction of graphite and elemental nitrogen (from decomposed NaN 3 ) with Sr 2 N at 1020 K yields for the first time a phase that contains the two triatomic anions acetonitriletriide C 2 N 3– and carbodiimide CN 2 2– side by side. Further synthetic routes were likewise successfully tested, including a sodium free approach (Sr 2 N + C) and the use of NaCN as carbon and nitrogen source. The monoclinic crystal structure is derived from powder and single-crystal X-ray diffraction data (P2 1 /c, a = 397.74(1) pm, b = 1411.72(3) pm, c = 692.57(1) pm, β = 103.57(1)°, Z = 2). The existence of both anions in Sr 4 N[CN 2 ][C 2 N] is further confirmed by IR and Raman spectroscopy. With its novel 1-D chain structure of edge-sharing NSr 6 octahedra, the material also enriches the structural variety of ternary alkaline earth metal nitrides.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Acetonitriletriide; Solid-state structures; Solid-state synthesis; Strontium; Vibrational spectroscopy